Analisis Pengaruh Relative Advantage, Complexity, Trialability dan Observability terhadap Niat Adopsi Cloud Accounting di Jakarta - de Gala, Brina Sitanggang; Aryati, Titik (BUDGETING : Journal of Business, Management and Accounting, 2024)
This research examines and analyzes the influence of relative advantage, complexity, trialability, and observability on intention to adopt cloud accounting in Jakarta. This research applies a quantitative approach using survey instruments and measuring variables using a Likert scale. The sampling method applied in this research is purposive sampling. The data source used in this research is primary data collected through questionnaires and distributed using the Google Form platform and distributed via social media such as Whatsapp, LinkedIn, Twitter and the Kudata platform. The number of samples used in this research was 218 samples. Data testing carried out included descriptive statistical analysis, validity testing, reliability testing, classical assumption testing, and hypothesis testing. The research results show that relative advantage, trialability and observability have a positive effect on cloud accounting adoption intentions. Meanwhile, complexity has a negative effect on cloud accounting adoption intentions. Therefore, accounting staff can adapt to dynamic technological innovation by investing in cloud accounting, which has high potential industry value. Using cloud accounting can also make it easier for accounting staff to manage their work better. Keywords: Cloud Accounting, Relative Advantage, Complexity, Trialability and Observability.